LECTURERS’ AND STUDENTS’ PERCEPTION OF SOCIAL MEDIA FOR TEACHING AND LEARNING DURING THE COVID-19 PANDEMIC: A CASE STUDY OF ACHIEVERS UNIVERSITY, OWO, NIGERIA - Omotehinwa, T. O.; Adeniyi, A. A.; Adenegan, T. S. (FUDMA JOURNAL OF SCIENCES, 2021)
This study examined the perception of lecturers and students of Achievers University, Owo, Nigeria, about the use of social media for teaching and learning during the COVID-19 pandemic. The study, was carried out on 123 lecturers and 487 students from the 4 existing colleges through 5-point Likert scale questionnaires administered online. Data collected were analyzed using t-test and ANOVA in addition to the descriptive statistics. The findings of this study show that, social media was perceived to be useful for teaching by lecturers while students have a negative perception about its usefulness and ease of use. The study recommends that lecturers must be exposed through seminars and conferences to the best practices for developing and delivering online courses to make online teaching very productive and enjoyable for both lecturers and students
Keywords: Social Media, Technology Acceptance Model (TAM), Online learning, Perceived Usefulness, Perceived Ease of Use, COVID-19